Омический делитель напряжения для измерения испытательных грозовых и коммутационных импульсов амплитудой до 1 МВ - Баранов, Михаил Иванович; Бочаров, Виталий Александрович; Зиньковский, В. М.; Зябко, Юрий Павлович; Игнатенко, Николай Николаевич (НТУ "ХПИ", 2007)
Описано конструкцію і технічні характеристики створеного пересувного високовольтного омічного дільника для виміру імпульсів напруги мікро- і мілісекундного часового діапазону амплітудою до 1 МВ і дані рекомендації з його практичного застосування в області техніки і електрофізики високих напруг.

The design and performance data of the movable high-voltage ohmic divider which was created for measurement of voltage pulses of micro- and millisecond time range with amplitudes up to 1MV are described, the recommendations on its practical application in the field of high-voltage engineering and electrophysics are given.
Keywords: высоковольтная импульсная техника; активные сопротивления; номинальное напряжение; апериодический импульс; высоковольтное плечо; омический делитель